“METÁFORA É QUE NEM...”: COGNIÇÃO E DISCURSO NA METÁFORA SITUADA - Solange Vereza (Signo, 2014)
“METAPHOR IS LKE...”: COGNITION AND DISCOURSE IN SITUATED METAPHORS ABSTRACT The aim of this paper is to propose an articulation between cognition and discourseas a conceptual tool to understand both the role of metaphor in language in use and the role of use in determining metaphoricity. To this end, besides a preliminary theoretical discussion, four texts of different genres, which have in common metaphorical language as a guiding process in meaning construction, will be analysed under the light of the concept of “situated metaphor”, to be elaborated here. This approach is inserted into the context of recent metaphor studies, which, together, form what can be thought of as ‘a discursive turn’ within the sociocognitive paradigm in metaphor research.